Instrumen Stimulus Fiskal: Pilihan Kebijakan dan Pengaruhnya terhadap Perekonomian - Wardhana, Wisynu; Hartono, Djoni (Jurnal Ekonomi dan Pembangunan Indonesia, 2012)
This study aims to identify the impact of the fiscal stimulus instrument choices on the economy, and to formulate policy options appropriate with the fiscal stimulus in boosting the economy, especially on economic growth, employment, and household income. The analysis tools is Applied General Equilibrium Model for Fiscal Policy Analysis (AGEFIS) using the Social Accounting Matrix database (SAM) of Indonesia in 2005. The simulation results show that (i) fiscal stimulus provide a boost to economic growth, employment, and household income, but on the other hand have a potential to cause an increase in price, (ii) government spending and cutting taxes on goods are the choice of instrument stimulus policies that provide the greatest multiplier effect in promoting economic growth, employment and household income.